2014
DOI: 10.4238/2014.december.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel single nucleotide polymorphism and imprinted status analysis of the Ras protein-specific guanine nucleotide-releasing factor 1 gene in domestic pigs

Abstract: ABSTRACT. The aim of this study was to determine the imprinting status of the Ras protein-specific guanine nucleotide-releasing factor 1 (Rasgrf1) gene in domestic pigs. In this study, a 228-bp partial sequence located in exon 14 and a 193-bp partial sequence located in exon 1 of the Rasgrf1 gene in domestic pigs were obtained. A novel single nucleotide polymorphism, a G/A transition, was identified in Rasgrf1 exon 14, and then the reciprocal Berkshire x Wannan black F1 hybrid model and the reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…While 56% (270/484) of DMRs in epiblasts were apparently established in gametes, 50% (2,749/5,462) of DMRs in EPCs were Table 1 List of canonically imprinted genes identified in the rat and mouse Pat Paternally methylated, Mat Maternally methylated, N.I. Not informative a Not annotated in rat b These genes are reported to be imprinted (expressed) in rats in previous studies [11] c One or more genes in the orthologous imprinted cluster have been reported to be imprinted in human, cow (and pig), or marsupials [11,35,[37][38][39][40][41][42][43][44]…”
Section: Identification Of Canonical Differentially Methylated Region...mentioning
confidence: 99%
“…While 56% (270/484) of DMRs in epiblasts were apparently established in gametes, 50% (2,749/5,462) of DMRs in EPCs were Table 1 List of canonically imprinted genes identified in the rat and mouse Pat Paternally methylated, Mat Maternally methylated, N.I. Not informative a Not annotated in rat b These genes are reported to be imprinted (expressed) in rats in previous studies [11] c One or more genes in the orthologous imprinted cluster have been reported to be imprinted in human, cow (and pig), or marsupials [11,35,[37][38][39][40][41][42][43][44]…”
Section: Identification Of Canonical Differentially Methylated Region...mentioning
confidence: 99%